Optimal N/P Ratio of the Shrimp Culture Waste Fertilizer For Growth Rate of Spirulina platensis - Widigdo, Syafrianur; Shofy Mubarak, Ahmad; Nurmalia Dewi, Nina (Universitas Airlangga, 2024)
The cultivation of vaname shrimp produces waste with a high nutrient content. This waste can be used as fertilizer in microalgae culture like Sprulina platensis. However, the N / P ratio in shrimp culture waste is low, namely 5.5: 1, while the need for growth of blue-green algae ranges from 10:1 - 16:1. Therefore, it is necessary to regulate the N: P ratio in shrimp culture waste to match the needs of S. platensis. The purpose of this study was to determine the effect of different N / P ratios on shrimp culture waste fertilizer on the growth of S. plantesis. This study used a Completely Randomized Design (CRD) which was divided into 6 treatments with 3 replications, as P0: Walne fertilizer (N / P ratio 17: 1), P1: shrimp culture waste fertilizer enriched with urea (N / P ratio 5,5: 1), P2 with N/P ratio of 10.5: 1, P3 with N/P ratio of 15.5: 1, P4 with N/P ratio of 20.5: 1 and P5 with N/P ratio 25.5: 1. The parameters observed were density and growth rate of S. platensis and water quality namely: temperature, salinity, and pH. The data obtained were processed using Analysis of Variance (ANOVA) and continued with Duncan's multiple range test. The results of this study indicate that the application of shrimp culture waste fertilizer with different N/P ratios affect the population and growth rate of S. platensis. Shrimp culture waste fertilizer with a N: P ratio of 15.5: 1 (P3) is the best treatment for the growth of S. platensis because it produces the highest population and growth rate compared to the other treatments.